Dever de informar do médico e o direito do paciente de ser informado na relação consumerista - Castro, João Monteiro de (2021)
The theme addressed in this work is the duty to inform imposed to the physician associated with the right to be informed of the patient (consumer) from the perspective of consumer law, respect for human dignity, autonomy and self-determination of the patient. The right of the patient (consumer) to be provided with information, in quantity and quality, that makes it possible to decide and establish prior, informed and free consent to the medical act is fundamental and respecting human dignity, autonomy and self-determination. This panorama remains maintained even with the technological escalation that has been shaping the exercise of medicine in the present and that is projected for the future. Without the patient (consumer) being properly informed, in terms of quality and quantity, there will be a failure of the service provided by the doctor. And even if damage under the technical-legal aspect is not inflicted on the patient, there will have indemnifiable damage, material and/or no material, for violation of the patient's right to information